Penataan Sarana Prasarana Pasar di Kawasan Perumahan Vila Mutiara Cikarang Tata Kota dan Daerah - Kerlima Hutagaol; Riza Fahlevi; Budi Harta Winata; Meliana Nur Evani (Pusat riset dan Inovasi Nasional, 2026)
A market is a place where buying and selling transactions take place between sellers and buyers at a specific time and place. This definition encompasses several key elements: the presence of sellers, buyers, a specific place and time, and a transaction agreement. Such markets are also known as traditional markets.